Nasomaxillary effects of miniscrew-assisted rapid palatal expansion and two surgically assisted rapid palatal expansion approaches - Jesus, A. S. [UNESP]; Oliveira, C. B. [UNESP]; Murata, W. H.; Gonçales, E. S.; Pereira-Filho, V. A. [UNESP]; Santos-Pinto, A. [UNESP] (Elsevier, 2021)
This retrospective study was performed to evaluate nasomaxillary changes in 36 patients at an advanced stage of skeletal maturity who underwent miniscrew-assisted rapid palatal expansion (MARPE) or surgically assisted rapid palatal expansion (SARPE) with/without an alar base cinch. Cone beam computed tomography images taken before and after expansion were analysed. Changes in the width of the dental arch (D66S, D66I), maxillary base (MxMol), and nasal floor and nasal cavity in the molar and canine regions (NaFMol, NaFCan, NaCMol, NaCCan) were compared, as well as changes in the choanal aperture (CA) and nasal soft tissue (NW). The MARPE technique produced smaller dental changes (D66S; P = 0.025) and greater nasomaxillary expansion (MxMol, P = 0.010; NaCMol, P = 0.016; NaCCan, P = 0.017; NaFMol, P = 0.001; CA, P = 0.002) than both SARPE techniques. Changes in NW did not differ significantly between the groups (P = 0.200). MARPE uniformly increased the anterior and posterior widths of the nasal cavity. SARPE expanded the nasal cavity in a ‘V-shape’ pattern. Changes in the nasal cavity and choanal aperture related to the amount of dental arch expansion were greater for MARPE than for SARPE. All three approaches increased the width of the nasal soft tissue, although the cinch in SARPE limited this increase.
Keywords: cone-beam computed tomography; distraction osteogenesis; Le Fort osteotomy; orthodontic anchorage procedures; palatal expansion technique